Strategi Komunikasi Keluarga Dalam Mengurangi Screen Time Anak Usia Dini di Desa Bartong Kabupaten Serdang Bedagai - Aina, Nurul (Universitas Muhammadiyah Sumatera Utara, 2025)
The development of technology in the digital era has changed the way of life in various aspects of life, including in patterns of interaction and daily activities. The use of electronic devices such as smartphones, tablets, and televisions has now become an inseparable part of human life, both adults and young children. The purpose of this study was to explain family communication strategies in reducing screen time for early childhood in Bartong Village, Serdang Bedagai Regency. The method used in this study is a descriptive qualitative research method. The research concept uses research categorization from the main aspects, namely Communicator, Message, Media, Communicant, and Feedback. Data collection was carried out by conducting interviews with five informants who were members of the community or families of children exposed to screen time. The data analysis technique used was qualitative, namely with data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that the approach of speaking softly and providing direct examples was more effective than the rules for limiting screen time. Parents divert children's attention with physical and social activities to reduce dependence on screen devices. Although the strategies implemented have proven effective, evaluation and adjustment of strategies are still needed for more optimal results.